2002
DOI: 10.1073/pnas.212504499
|View full text |Cite
|
Sign up to set email alerts
|

Three semidominant barley mutants with single amino acid substitutions in the smallest magnesium chelatase subunit form defective AAA + hexamers

Abstract: Many enzymes of the bacteriochlorophyll and chlorophyll biosynthesis pathways have been conserved throughout evolution, but the molecular mechanisms of the key steps remain unclear. The magnesium chelatase reaction is one of these steps, and it requires the proteins BchI, BchD, and BchH to catalyze the insertion of Mg 2؉ into protoporphyrin IX upon ATP hydrolysis. Structural analyses have shown that BchI forms hexamers and belongs to the ATPases associated with various cellular activities (AAA ؉ ) family of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(113 citation statements)
references
References 48 publications
(68 reference statements)
5
107
1
Order By: Relevance
“…This inhibitory or poisoning effect of the mutant I subunits on the wild-type I subunits was >50% at a 1:1 ratio in the R. capsulatus system, whereas a threefold to ninefold excess of mutant subunits over wild-type protein was required to obtain a 50% inhibition in Synechocystis. These experiments demonstrated the dominant effect of the proteins in vitro, and it was concluded that the I subunits function in a concerted manner within the hexameric complex (Hansson et al, 2002).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…This inhibitory or poisoning effect of the mutant I subunits on the wild-type I subunits was >50% at a 1:1 ratio in the R. capsulatus system, whereas a threefold to ninefold excess of mutant subunits over wild-type protein was required to obtain a 50% inhibition in Synechocystis. These experiments demonstrated the dominant effect of the proteins in vitro, and it was concluded that the I subunits function in a concerted manner within the hexameric complex (Hansson et al, 2002).…”
Section: Introductionmentioning
confidence: 92%
“…Previous analyses of semidominant and recessive barley and maize (Zea mays) Mg-chelatase mutants deficient in the I subunit have also provided knowledge on the interactions between the subunits (Hansson et al, , 2002Sawers et al, 2006). The D subunit could not be detected in any of the studied barley I mutants, whereas wild-type levels of the D subunit were found in barley mutants that lacked the H subunit (Lake et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the four preceding enzymatic steps ( Figure 1A), reduced Mg-chelatase activity does not cause photosensitivity, but rather reduced chlorophyll levels due to a negative feedback regulatory mechanism (Hansson et al, 1999(Hansson et al, , 2002Papenbrock et al, 2000aPapenbrock et al, , 2000bSoldatova et al, 2005;Sawers et al, 2006). The substrate of Mg-chelatase, protoporphyrin IX, is the branch point of chlorophyll and heme synthesis ( Figure 1A); by contrast, antisense suppression of the first committed heme synthetic enzyme, plastidic ferrochelatase, does lead to protoporphyrin IX accumulation and light-dependent necrosis (Papenbrock et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggested that intracellular Ca 2+ -Mg 2+ -ATPase activity was not only dependent on the level of its gene expression but also was affected by many other factors [17][18][19] .…”
Section: Activity and Expression Of Intracellularmentioning
confidence: 93%